2016
DOI: 10.1016/j.ijid.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated colistin resistance in Escherichia coli from the Arabian Peninsula

Abstract: This is the first report on the presence of the plasmid-coded mcr-1 gene in a variety of multi-resistant clinical isolates from the Arabian Peninsula indicating that several commonly used antibiotics can potentially facilitate the spread of mcr-1 carrying strains, or directly, mcr-1 containing plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 26 publications
5
62
1
Order By: Relevance
“…KX013538), isolated from a pathogenic human E . coli in the United Arab Emirates [31], and pHNSHP45 (KP347127) the first reported pMCR [1]. The other 2 pMCRs (from M19736 and M19855) were more similar to plasmid pECJS-61-63 (KX084393) from an E .…”
Section: Resultsmentioning
confidence: 99%
“…KX013538), isolated from a pathogenic human E . coli in the United Arab Emirates [31], and pHNSHP45 (KP347127) the first reported pMCR [1]. The other 2 pMCRs (from M19736 and M19855) were more similar to plasmid pECJS-61-63 (KX084393) from an E .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study by Sonnevend et al also showed that mcr-1 is present in Bahrain, where it was detected in two E. coli isolates cultured from human clinical samples (23). In silico MLST assigned the isolate to ST-617, a member of the globally distributed clonal complex 10 (CC10) and part of phylogenetic group A, which is most often associated with commensal E.…”
Section: Discussionmentioning
confidence: 97%
“…Though the E. coli strains in the study of Sonnevend et al belonged to different STs (ST-648 and ST-224), both carried mcr-1 on an IncI2 plasmid (23). …”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the colistin resistance gene mcr-1, an increasing number of plasmids carrying this resistance determinant have been reported, among which the ϳ60-kb IncI2 plasmid was one of the three common types of conjugative mcr-1-bearing plasmids (1,2). This IncI2 plasmid has been reported to carry an additional bla CTX-M-55 or bla CTX-M-64 gene (2,3). In this study, we report the recovery of a similar IncI2-type mcr-1-bearing conjugative plasmid that harbors a novel variant of bla CTX-M-64 , which encodes resistance to class A ␤-lactamase inhibitors.…”
mentioning
confidence: 99%